2014
DOI: 10.6000/1927-5129.2014.10.31
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Efficacy of C1-C2 Sustained Natural Apophyseal Glide (SNAG) Versus Posterior Anterior Vertebral Mobilization (PAVMs) in the Management of Cervicogenic Headache

Abstract: Objectives: To determine the effect of a C1-C2 sustained natural apophyseal glide (SNAG) as compare to posterior anterior (PA) vertebral mobilization on cervicogenic headache.Study Design: Randomized Control Trial.Method: The study was conducted on 60 patients with CGH. In this study, patients were divided into two groups, group A and group B equally. Group A of 30 patients received SNAG and at the same time Group B of 30 patients were treated with PAVMs. A pre tested and structured questionnaire was used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…One of the other two studies investigated dosage effects of SMT on CEH ( 20 ), and the other compared the effectiveness of two different forms of SMT for individuals with CEH ( 23 ). Haas et al ( 20 ) looked at the relationship between treatment frequency and patient outcomes for subjects receiving one, three, or four treatments per week.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the other two studies investigated dosage effects of SMT on CEH ( 20 ), and the other compared the effectiveness of two different forms of SMT for individuals with CEH ( 23 ). Haas et al ( 20 ) looked at the relationship between treatment frequency and patient outcomes for subjects receiving one, three, or four treatments per week.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that there may be an optimal dosage effect for SMT intervention and that, to a certain extent, more frequent treatments may be related to more significant positive outcomes. Khan et al ( 23 ) examined how a SNAG intervention compared to posterior anterior vertebral mobilization (PVAM) in treating CEH. Their research revealed that although both groups had improvements in neck disability index (NDI) and visual analog (VAS) scores, the SNAG treatment group was more effective for both NDI ( p = 0.004) and VAS ( p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…are painful and can have serious complication if not done correctly and can cause increase in pain and may cause hearing loss and other symptoms. [5][14][17] [18] This show that our intervention has resulted significant changes in the hearing ability which in turn that the misaligned upper cervical can result in sympathetic disturbance.…”
Section: Discussion:-mentioning
confidence: 99%
“…CH is common in clinical practice seen and routinely treated, but limited research and experts lack of consensus by is one of the subjects (6,15) and the effectiveness of its techniques has not yet been determined (3). To the best of our knowledge, there are only a few studies in the literature regarding the effectiveness of Mulligan mobilization technique in patients with CH (16)(17)(18). Two of these studies compared Mulligan mobilization with the placebo group (17,18) while the other study compared it with another mobilization technique (16).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are only a few studies in the literature regarding the effectiveness of Mulligan mobilization technique in patients with CH (16)(17)(18). Two of these studies compared Mulligan mobilization with the placebo group (17,18) while the other study compared it with another mobilization technique (16). However, there is no study on the effectiveness of only conventional physical therapy consisting of hot pack, US, TENS and exercise therapy.…”
Section: Introductionmentioning
confidence: 99%